Bahasa English : Bahasa English - Farin Oktafia Safitri, Isti (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2025)
Maladevis Beach in Paciran, Lamongan, holds unique potential through the Petik Laut tradition as a cultural tourism attraction. However, this potential has not been optimally managed due to the lack of a structured, community-centered development strategy. Therefore, this study aims to formulate a sustainable tourism development strategy at Maldives Beach by analyzing internal and external factors and integrating them within a Community-Based Tourism (CBT) framework. This research employed a qualitative approach with a case study design. Data collection was conducted through in-depth interviews, observations, and structured questionnaires with key informants consisting of community leaders, tourism managers, and local government representatives. The collected data were analyzed quantitatively using the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices to map the strategic position.The study's key findings indicate that Maladevis Beach is in Quadrant I (Aggressive Growth Strategy) with a total IFAS score of 0.40 and an EFAS score of 0.80. This position confirms that internal strengths, dominated by the unique Petik Laut tradition, along with favorable external opportunities, significantly outweigh managerial weaknesses and existing threats. As a result, this study concluded that the most effective strategy was the implementation of a CBT model focused on community capacity building programs and the development of authentic tourism products. This model is recommended as a practical guide for transforming cultural potential into competitive and sustainable tourism destinations.